A Security Refreshing Algorithm of Dynamic Node based on Fast Group-Blind Signature. (June 2020) - Fan, Hongbin; Rao, Jiamin
Abstract: In the contemporary society, electronic payment becomes a part of people's life. It can make people's life more convenient and faster. At the same time, security's problem and efficiency's problem in the electronic payment arouse the attention of many researchers. In this paper, we study group-blind signature algorithms in digital signature technology. We take LR98 group-blind signature algorithm as the research object and analyze its problems. The algorithm put the fixed value l as security parameter, which results in the low efficiency of algorithm. In this paper, new security parameters are adopted, and take blind signature method of Boldyreva into consideration, a new group-blind method is proposed, CL-LR98. New method is applied to wireless communication network (WSN). A number of communication nodes (AP) and user terminal (UE) are built, which is used as the experimental environment. New group-blind signature method is applied to dynamic refreshing of WSN nodes, which includes anonymous communication, data transmission. In the process of experiments, new group-blind method has excellent characteristics, it has short signature character length, it can be simply realized and it has better encryption performance. In the node joining part and revocation part of communication process, these excellent characteristics make computation small, make node refresh efficiency high, and it will not cause frequent movement of other communication nodes.